Audit Opinion and Audit Report Lag - Galuh Artika Febriyanti (ITB AAS INDONESIA, 2022)
Financial statements are one of the sources of information used by internal and external parties of a company for decision making. These statements are audited by a public accountant, hence the presented information go through an independent assessment process. The accountants are required to complete the audit reports on time, but many issuers still do not publish financial statements early, so leading to an audit report lag. Therefore, this study aims to determine the effect of audit opinion, audit tenure, and firm size on the report lag. The companies involved were basic and chemical industries that published financial statements in rupiah between 2019-2020. Furthermore, the total population was 160 manufacturing companies listed on the Indonesia Stock Exchange in 2019-2020. The sample consisted of 124 companies that met the criteria and the multiple linier regression test was used. The results showed audit opinion had a significant effect on report lag, while the firm size and audit tenure had no significant effect.